MEMBANGUN DESAIN WEB FLEKSIBEL MENGGUNAKAN BOOTSTRAP 5: SOSIALISASI DI TBM KOLONG CIPUTAT - Eka Sri Rahayu; Nilovar Asyiah; Nurhasanah (Abdi Jurnal Publikasi, 2025)
Enhancing community understanding of web technology is a strategic step in addressing the demands of the digital era. In a socialization program at the Taman Bacaan Masyarakat (TBM) Kolong Ciputat, we introduced the concept of flexible web design utilizing Bootstrap 5. This framework offers ready-to-use components and a grid system that simplifies the creation of responsive designs. This article explores the methods implemented during the program, the outcomes achieved, and the evaluation of its effectiveness. The results indicate that participants successfully grasped fundamental concepts and implemented Bootstrap 5 to develop responsive web designs.